A composite copper current collector based on ligand oxidation structure adaptive strategy, a preparation method thereof, an electrode sheet and a battery
Patent Information
- Application Number
- CN202611092535.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
本发明旨在解决现有复合铜集流体铜层易氧化腐蚀、传统防腐技术牺牲导电性、防护耐久性差、钝化结构静态无自适应能力、工艺复杂且易破坏基材结构的技术短板,提供一种基于配体氧化结构自适应策略的复合铜集流体及其制备方法、极片和电池
本发明提出了一种配体氧化结构自适应改性方法,针对复合铜集流体铜层易氧化腐蚀、传统改性技术无法兼顾导电性与结构稳定性的问题,采用同时携带邻苯二酚基团与芳香胺基团的双功能小分子配体,在复合铜集流体铜层表面实现可控自组装成膜。其中,邻苯二酚基团可与铜层表面不同价态铜原子及铜氧化物产生强配位作用,使配体能够均匀、牢固地固结在铜层表面,自发形成超薄、连续、无晶界缺陷的初始纳米钝化薄膜,构建基础物理阻隔结构。当集流体处于腐蚀、高温、高湿等复杂工况时,膜层触发氧化诱导结构自适应演化:邻苯二酚基团氧化生成醌基,并进一步与铜离子构建高密度配位交联网络;与此同时,芳香胺基团氧化形成自由基阳离子,该阳离子与醌基芳香共轭骨架发生分子间阳离子-π相互作用,持续压缩膜层内部微观孔隙,促使钝化层由疏松结构向致密结构动态重构,实现钝化层的腐蚀工况自强化,从根本上改变传统钝化膜结构固定、防护能力单一的缺陷。同时,本发明采用的室温甲醇体系静态浸泡自组装工艺,无需高温、高压、电沉积等复杂改性手段,可在不破坏复合集流体层间结构、不遮挡铜导电通路的前提下,完成均匀钝化层的原位构建,适配多种基材与铜层结构规格。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a composite copper current collector based on an adaptive strategy of ligand oxidation structure, its preparation method, electrode, and battery. Background Technology
[0002] With the rapid development of new energy and electronic technology, the requirements for cycle life, safety performance, energy density, and structural stability of power batteries, flexible electronic devices, and semiconductor devices are constantly increasing. As a core component of the battery, the current collector is mainly used to collect the current generated by the battery's active materials and form a large current for external output. Its electrical and thermal conductivity, corrosion resistance, and interlayer structural stability directly determine the battery's service life and safety. Currently, commercial lithium-ion and sodium-ion batteries mostly use traditional copper and aluminum foil as current collectors for their positive and negative electrodes. These pure metal foils suffer from high cost and high density, severely restricting battery cost control and energy density breakthroughs. Therefore, lightweight and highly safe composite foil current collectors have become the mainstream of industry research and development. They employ a sandwich structure of "polymer substrate - metal conductive layer," leveraging the thin metal layer and lightweight polymer substrate to effectively reduce the overall weight of the current collector and increase battery energy density. Furthermore, the metal layer is easily broken during thermal runaway, which can block internal battery reactions and significantly improve battery safety performance. However, the copper metal layer of existing composite copper current collectors is highly susceptible to oxidation and corrosion when exposed to air, electrolytes, and humid, hot, and saline-alkali conditions. This leads to decreased conductivity, interlayer delamination, and structural failure, severely limiting their long-term service capability. Current mainstream copper layer corrosion modification technologies have significant technical shortcomings, failing to simultaneously achieve high conductivity, strong corrosion resistance, structural stability, and industrial adaptability. Specific deficiencies are as follows: Coating protection method: By depositing a thick layer of inorganic or organic anti-corrosion coating on the surface of the copper layer to isolate the corrosive medium, the thick coating will significantly block the conductive path of the copper layer, significantly sacrificing the inherent electrical and thermal conductivity of copper. At the same time, the coating has poor interfacial compatibility with the copper layer and polymer substrate, weak bonding force, and is prone to cracking and peeling under long-term bending and humid heat conditions, resulting in poor protective durability. Molecular inhibition method: Small molecule corrosion inhibitors are directly dissolved in battery electrolytes or corrosive media to exert a protective effect. This method is a passive protection and can only be adapted to specific mild operating conditions. The protective effect disappears immediately after the corrosion inhibitor is consumed. It cannot meet the long-term and stable service requirements of composite current collectors and has extremely poor versatility. Traditional molecular passivation methods: Conventional liquid-phase molecular immersion passivation is a static, passive protection technology, generally suffering from weak protective performance and lack of self-upgrading capabilities. Furthermore, most modified systems require complex processes such as hydrothermal treatment, high-temperature chemical grafting, and electrodeposition to achieve molecular immobilization. This is not only cumbersome and energy-intensive, resulting in high mass production costs, but the harsh reaction conditions can easily damage the polymer substrate and disrupt the interlayer structure integrity of the composite current collector. Simultaneously, traditional molecular passivation layers are fixed and static structures with high porosity and insufficient density, lacking environmentally responsive adaptive strengthening capabilities and limited corrosion resistance. They are ill-suited for extreme and complex operating conditions such as high temperature, high humidity, salinity, and ultraviolet radiation, and cannot meet the long-term service requirements of composite copper current collectors. In summary, current composite copper current collector corrosion protection technologies generally suffer from technical bottlenecks such as sacrificing conductivity, poor protective durability, complex processes, weak adaptability to operating conditions, and easy damage to the substrate structure. The industry urgently needs to develop an adaptive modification technology that is simple, green, mild, and industrially mass-producible, while simultaneously ensuring high electrical and thermal conductivity, strong corrosion resistance, and stable interlayer structure of composite copper current collectors. Summary of the Invention This invention aims to address the shortcomings of existing composite copper current collectors, such as easy oxidation and corrosion of the copper layer, sacrifice of conductivity by traditional anti-corrosion technologies, poor protective durability, lack of self-adaptive capability in static passivation structures, and complex processes that easily damage the substrate structure. It provides a composite copper current collector based on a ligand oxidation structure adaptive strategy, its preparation method, electrode, and battery.
[0003] To achieve the above objectives, the technical solution provided by the present invention is as follows: The first aspect of this application provides a composite copper current collector based on an adaptive strategy of ligand oxidation structure, including a polymer substrate in the center layer, copper layers on both sides of the polymer substrate, and ligand passivation nanolayers respectively disposed on the copper layers on both sides. The ligand passivation nanolayer is a structured self-assembled film of bifunctional small molecule ligands, which completely covers and is fixed to the surface of the copper layer. The bifunctional small molecule ligand contains both a catechol active group that can coordinate with copper and an aromatic amine active group that can be oxidized to generate free radical cations, which enables the ligand passivation nanolayer to have an oxidative self-adaptive property that can achieve structural compactness enhancement through group oxidation crosslinking reconstruction under corrosion conditions.
[0004] To optimize the above technical solution, the specific limitations also include: The thickness of the polymer substrate is 10–100 μm, the thickness of the copper layer on one side of the polymer substrate is 1–50 μm, and the thickness of the ligand passivation nanolayer is 2–30 nm.
[0005] Furthermore, the bifunctional small molecule ligand is any one of the following: a three-armed catechol-triphenylamine compound, a naphthol-catechol-amine compound, a triphenylamine-catechol compound, or a triazine-catechol-amine compound.
[0006] A second aspect of this application provides a method for preparing the aforementioned composite copper current collector based on an adaptive strategy of ligand oxidation structure, comprising the following steps: S1: Cleaning, removing impurities, and drying the polymer substrate for pretreatment; S2: A uniform copper layer is deposited on both sides of the pretreated polymer substrate to obtain a copper composite substrate; S3: The copper composite substrate obtained after depositing the copper layer is placed in a bifunctional ligand solution at room temperature to complete the ligand self-assembly and form the initial ligand passivation nanolayer. S4: After soaking, the composite substrate is cleaned and dried to remove free ligands on the surface, thus obtaining the target composite copper current collector.
[0007] In step S1, the polymer substrate is pretreated by cleaning, removing impurities, and drying as follows: the polymer substrate is ultrasonically cleaned with anhydrous ethanol and deionized water for 10-30 minutes in sequence, and then dried with nitrogen.
[0008] In step S2, the process for depositing a uniform copper layer is any one of magnetron sputtering, electroplating, or thermal evaporation; wherein, after the thermal evaporation deposition process is completed, a low-temperature annealing treatment is performed.
[0009] In step S3, the solvent of the bifunctional ligand solution is methanol, the concentration of the bifunctional ligand solution is 0.01-1 mM, the immersion temperature is 20-25℃, and the immersion time is 10-36 h.
[0010] In step S4, the post-treatment method is as follows: ultrasonic cleaning with anhydrous methanol for 5-10 minutes to remove uncoordinated free ligands, and finally drying with nitrogen at a constant temperature.
[0011] A third aspect of this application provides an electrode comprising the aforementioned composite copper current collector based on an adaptive strategy for ligand oxidation structure.
[0012] A fourth aspect of this application provides a battery comprising the aforementioned electrode.
[0013] Compared with the prior art, the beneficial effects of the present invention are: This invention proposes an adaptive modification method for ligand oxidation structure. Addressing the issues of easy oxidation and corrosion of the copper layer in composite copper current collectors and the inability of traditional modification techniques to simultaneously achieve conductivity and structural stability, this invention employs bifunctional small-molecule ligands carrying both catechol and aromatic amine groups to achieve controllable self-assembly into a film on the surface of the copper layer in the composite copper current collector. The catechol groups can generate strong coordination with copper atoms and copper oxides of different valence states on the copper layer surface, enabling the ligands to uniformly and firmly adhere to the copper layer surface, spontaneously forming an ultrathin, continuous, and defect-free initial nano-passivation film, thus constructing a basic physical barrier structure. When the current collector is subjected to complex conditions such as corrosion, high temperature, and high humidity, the film layer triggers an oxidation-induced adaptive evolution of its structure: catechol groups are oxidized to generate quinone groups, which further construct a high-density coordination cross-linking network with copper ions; simultaneously, aromatic amine groups are oxidized to form free radical cations, which undergo intermolecular cation-π interactions with the quinone aromatic conjugated framework, continuously compressing the micropores inside the film layer and promoting the dynamic reconstruction of the passivation layer from a loose structure to a dense structure, achieving self-reinforcement of the passivation layer under corrosion conditions, fundamentally changing the defects of traditional passivation films with fixed structures and limited protective capabilities. Furthermore, the room-temperature methanol system static immersion self-assembly process used in this invention does not require complex modification methods such as high temperature, high pressure, or electrodeposition, and can complete the in-situ construction of a uniform passivation layer without damaging the interlayer structure of the composite current collector or blocking the copper conductive path, adapting to various substrates and copper layer structure specifications.
[0014] This invention achieves dynamic adaptive protection of the passivation layer, significantly improving structural stability. The modified film layer of this invention possesses environmentally responsive structural reconstruction capabilities, and can autonomously densify and strengthen under corrosive conditions, effectively blocking the intrusion of external corrosive media. It solves the problems of easy failure and poor protective durability of traditional passivation layers during long-term service, and significantly improves the alkali resistance, salt spray resistance, high temperature resistance, and UV aging resistance of the composite copper current collector.
[0015] The passivation layer formed by this invention is a nanoscale ultrathin continuous structure, free from insulation defects, preserving the inherent conductive and thermal conductivity pathways of the copper layer to the greatest extent, and balancing high protection performance with excellent electrical and thermal conductivity. The modified current collector has electrical and thermal conductivity properties close to those of a pure copper substrate, and its performance degradation under long-term corrosion conditions is extremely low, overcoming the technical drawback of traditional thick coating protection that sacrifices conductivity.
[0016] The composite copper current collector of the present invention has strong interlayer bonding force, excellent mechanical and structural stability, and the ligands and copper layers are solidified by chemical bonding. The interface is tightly bonded and is not prone to peeling or detachment. It can withstand repeated bending, peeling and other mechanical actions, and completely preserve the interlayer structure integrity of the composite current collector. Detailed Implementation
[0017] The present invention will be further described in detail below through specific embodiments, but it should not be construed as limiting the scope of the subject matter of the present invention to the following embodiments. All technologies implemented based on the above content of the present invention fall within the scope of the present invention.
[0018] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the reagents, methods and equipment used are conventional reagents, methods and equipment in this technical field.
[0019] This invention provides a composite copper current collector based on an adaptive strategy of ligand oxidation structure, comprising a polymer substrate in the center layer, copper layers on both sides of the polymer substrate, and ligand passivation nanolayers respectively disposed on the copper layers on both sides. The ligand passivation nanolayer is a structured self-assembled film of bifunctional small molecule ligands, which completely covers and is bonded to the surface of the copper layer. The bifunctional small molecule ligand contains both catechol active groups that can coordinate with copper and aromatic amine active groups that can be oxidized to generate free radical cations, which enables the ligand passivation nanolayer to have the ability to achieve structural compactness enhancement through group oxidation crosslinking reconstruction under corrosion conditions.
[0020] The composite copper current collector of this invention differs from the traditional composite copper current collector with its single-layer copper structure lacking adaptive passivation protection. The bifunctional small molecule ligand possesses dual active group characteristics: the catechol active group can undergo a stable coordination reaction with the metal sites on the copper layer surface, achieving high-strength consolidation and adhesion of the ligand film on the copper layer surface; the aromatic amine active group can undergo an oxidation reaction under complex working conditions such as corrosion, high temperature, humid heat, and ultraviolet irradiation to generate free radical cations, triggering cross-linking and reconstruction between ligand molecules.
[0021] The ligand passivation nanolayer is a structured thin film formed by in-situ self-assembly, rather than a simple coating. It can completely conform to the microscopic morphology of the copper layer surface, without pores or gaps, and physically blocks contact between the copper substrate and corrosive media such as air, electrolyte, and humid heat and salt alkali. At the same time, this passivation layer is a dynamically responsive structure, overcoming the shortcomings of traditional passivation layers that are fixed, static, and passively protective. It has the ability to adapt and strengthen under working conditions, and belongs to a modified liquid-phase molecular passivation structure. There is no substrate damage or conductive path obstruction defects throughout the process.
[0022] This structure relies on a bifunctional ligand coordination consolidation and oxidation adaptive strengthening mechanism, which not only ensures extremely strong interfacial bonding between the passivation layer and the copper layer, solving the problems of easy cracking and detachment and poor durability of traditional protective layers, but also can autonomously improve the protective density under extreme working conditions, significantly enhancing the corrosion resistance and aging resistance of the current collector. At the same time, the ultra-thin self-assembly structure retains the inherent electrical and thermal conductivity of the copper layer to the greatest extent, taking into account high conductivity, structural stability and adaptability to complex working conditions, completely solving the technical problems of traditional anti-corrosion technology that sacrifice conductivity, fixed protective capabilities and easy structural failure.
[0023] In some embodiments, the thickness of the polymer substrate is 10–100 μm, the thickness of the copper layer on one side of the polymer substrate is 1–50 μm, and the thickness of the ligand passivation nanolayer is 2–30 nm.
[0024] The ultra-thin nano-passivation layer of 2–30 nm forms a complete and dense anti-corrosion barrier without obstructing the conductive path of the copper layer. This results in zero sacrifice of the current collector's electrical and thermal conductivity, ensuring the battery's high-current output capability. The thickness ratio of the substrate, copper layer, and passivation layer achieves a balance between lightweight current collector and high conductivity, effectively reducing the overall battery weight, contributing to increased battery energy density, and overcoming the limitation of high density in traditional pure copper foil, which restricts breakthroughs in battery energy density.
[0025] In some embodiments, the bifunctional small molecule ligand is any one of three-armed catechol-triphenylamine compounds, naphthol-catechol-amine compounds, triphenylamine-catechol compounds, and triazine-catechol-amine compounds.
[0026] Among them, the three-armed catechol-triphenylamine compound and the triphenylamine-catechol compound have a stable aromatic amine conjugated structure, high oxidation response sensitivity and good crosslinking reconstruction uniformity; the naphthol-catechol-amine compound and the triazine-catechol-amine compound have excellent structural stability and strong weather resistance, and can be adapted to long-term extreme working conditions.
[0027] This invention also provides a method for preparing a composite copper current collector based on an adaptive strategy of ligand oxidation structure, comprising the following steps: S1: Cleaning, removing impurities, and drying the polymer substrate for pretreatment; S2: A uniform copper layer is deposited on both sides of the pretreated polymer substrate to obtain a copper composite substrate; S3: The copper composite substrate obtained after depositing the copper layer is placed in a bifunctional ligand solution at room temperature to complete the ligand self-assembly and form the initial ligand passivation nanolayer. S4: After soaking, the composite substrate is cleaned and dried to remove free ligands on the surface, thus obtaining the target composite copper current collector.
[0028] The preparation method of this invention is a fully room temperature and liquid phase self-assembly process, abandoning the complex and demanding processes of traditional hydrothermal, high-temperature grafting, and electrodeposition. The overall process is simple, requires no external energy input, and has no stringent reaction conditions. Step S1 completes the substrate pretreatment, thoroughly removing impurities and oil stains from the substrate surface, laying the foundation for the subsequent uniform deposition of the copper layer; Step S2 achieves uniform copper layer deposition on both sides, constructing a lightweight composite conductive substrate; Step S3 is the core adaptive passivation forming process, achieving autonomous coordination and self-assembly of bifunctional ligands through room temperature static immersion, generating an initial ultrathin and dense passivation layer in situ; Step S4 removes free ligands from the surface, retaining the stable and solidified functional passivation structure, obtaining the finished composite copper current collector.
[0029] In step S1, the polymer substrate is pretreated by cleaning, removing impurities, and drying as follows: the polymer substrate is ultrasonically cleaned with anhydrous ethanol and deionized water for 10-30 minutes in sequence, and then dried with nitrogen.
[0030] In step S2, the process for depositing a uniform copper layer is any one of magnetron sputtering, electroplating, or thermal evaporation; wherein, after the thermal evaporation deposition process is completed, a low-temperature annealing treatment is performed.
[0031] In step S3, the solvent of the bifunctional ligand solution is methanol, the concentration of the bifunctional ligand solution is 0.01-1 mM, the immersion temperature is 20-25℃, and the immersion time is 10-36 h.
[0032] In step S4, the post-treatment method is as follows: ultrasonic cleaning with anhydrous methanol for 5-10 minutes to remove uncoordinated free ligands, and finally drying with nitrogen at a constant temperature.
[0033] The present invention also provides an electrode comprising the above-described composite copper current collector based on the adaptive strategy of ligand oxidation structure.
[0034] The present invention also provides a battery comprising the above-described electrode.
[0035] This invention employs a composite copper current collector with adaptive ligand oxidation structure as the core conductive substrate, replacing traditional pure copper foil and ordinary composite copper current collectors. Leveraging the lightweight, high conductivity, adaptive corrosion resistance, and high structural stability of the composite copper current collector, the electrode, after loading with battery active materials, achieves overall lightweighting, high structural stability, and highly uniform conductivity, while also possessing adaptive corrosion resistance and anti-aging capabilities. This battery is suitable for various applications such as power batteries, flexible electronic devices, and semiconductor energy storage devices, and can withstand complex and extreme conditions such as high temperature, high humidity, salinity, and ultraviolet radiation, exhibiting long-term stable service capability.
[0036] The technical solution of the present invention will be further described in detail below with reference to specific embodiments: Example 1 In this embodiment, the ambient temperature was controlled at 20–25°C throughout the preparation process. The ligand solvent used was analytical grade anhydrous methanol with a purity ≥99.7%. The unified testing conditions included a 0.1M NaOH alkaline corrosion system, a 0.1M NaCl + 0.1M NaOH mixed salt-alkali corrosion system, and a 98% humidity + UV11 ultraviolet + 50°C high-temperature humid environment chamber. The percentage of corrosion area in different cycles, conductivity attenuation rate, and surface structure integrity were used as unified evaluation indicators. The specific preparation steps are as follows: (1) Substrate pretreatment: Select PET polymer substrate with a thickness of 50μm, and clean it with anhydrous ethanol and deionized water for 20min each to remove surface oil, dust and impurities. Then dry it with high-purity nitrogen at a constant temperature for later use.
[0037] (2) Copper layer deposition: A copper layer with a thickness of 25 μm is uniformly deposited on both sides of the polymer substrate using an electroplating process to obtain a composite substrate with copper layers on both sides.
[0038] (3) Ligand self-assembly passivation: Prepare a methanol solution of TAC bifunctional ligand (three-arm catechol-triphenylamine compound, purity ≥98%) with a concentration of 0.1 mM, immerse the composite substrate in the solution, and let it stand at room temperature for 24 h.
[0039] (4) Post-processing: Take out the substrate, use anhydrous methanol for ultrasonic cleaning for 8 min to remove uncoordinated free ligands on the surface, and blow dry with high-purity nitrogen at constant temperature to finally form a dense ligand passivation nanolayer with a thickness of 15 nm, and obtain the target composite copper current collector.
[0040] Example 2 This embodiment only changes the type of bifunctional ligand, using an NPC-Canaphthol-catechol-amine compound; all other preparation parameters and process steps remain the same as in the optimal embodiment 1. A 0.1 mM NPC-Ca methanol solution was prepared and the same PET / copper composite substrate was immersed at room temperature for 24 hours, followed by standardized post-treatment to obtain the finished product.
[0041] Example 3 In this embodiment, the ligand solution concentration is adjusted to 0.01mM, while the rest of the process, substrate, duration, and post-treatment are the same as in Example 1. This can stably form a complete and continuous passivation film with a thickness of about 2nm, which is suitable for low-concentration and mild self-assembly conditions.
[0042] Example 4 In this embodiment, the concentration of the ligand solution is adjusted to 1 mM, while the other parameters are the same as in Example 1. The high concentration of ligand can fully coordinate and grow, forming a dense passivation layer of nearly 30 nm without agglomeration defects, which is suitable for high-concentration rapid film formation process.
[0043] Example 5 This embodiment replaces the copper layer deposition process with a thermal evaporation + low-temperature annealing process. A 50μm PP substrate is selected, and a 25μm double-sided copper layer is deposited by thermal evaporation and then annealed at 100℃ for 60 min to eliminate internal stress. Subsequently, the finished product is prepared by soaking in 0.1mM TAC ligand for 24 h and conventional post-treatment.
[0044] Example 6 In this embodiment, only the soaking time is adjusted to 10 hours, and the other parameters are the same as in Embodiment 1. An ultrathin continuous passivation layer with a thickness of about 6 to 8 nm is formed through short-time coordination self-assembly.
[0045] Example 7 In this embodiment, only the soaking time was adjusted to 36 hours, and the other parameters were the same as in Example 1. Through long-term and sufficient coordination growth, a dense thick passivation layer with a thickness of about 27 to 30 nm was formed.
[0046] Comparative Example 1 The complete set of processes for substrate pretreatment, copper plating and post-treatment in Example 1 was followed, with the only difference being the omission of the bifunctional ligand self-assembly passivation core step, in which a pure composite copper current collector without any passivation nanolayer was prepared.
[0047] Comparative Example 2 Following the complete preparation process of Example 1, only the bifunctional ligand methanol solution was replaced with an equal volume of pure anhydrous methanol solvent, and no bifunctional ligand component participated in the reaction throughout the process.
[0048] Comparative Example 3 The preparation process and parameters are the same as in Example 1, except that the bifunctional ligand of the present invention, which has both catechol consolidation and aromatic amine response, is replaced with a single catechol monofunctional ligand. Lacking an oxidative adaptive active group, it cannot undergo oxidative crosslinking reconstruction and pore adaptive regulation.
[0049] Comparative Example 4 The overall process remains the same as in Example 1, except that the concentration of the ligand solution is adjusted to 0.005 mM.
[0050] Comparative Example 5 The overall process remains the same as in Example 1, except that the concentration of the ligand solution is adjusted to 1.5 mM.
[0051] Comparative Example 6 Using the same preparation system as in Example 1, only the soaking and passivation time was shortened to 5 hours. Due to the short duration, the coordination reaction was incomplete and the passivation film layer was not grown sufficiently, resulting in a defective and discontinuous ultrathin film layer.
[0052] Comparative Example 7 Using the same preparation system as in Example 1, only the soaking and passivation time was extended to 48 hours. Due to the excessive time, the ligand molecules were over-stacked, the film layer became redundantly thickened, and the interfacial stress accumulated excessively.
[0053] Comparative Example 8 The static passivation process using commercially available small molecule corrosion inhibitors was used to replace the oxidation adaptive ligand system of the present invention. The remaining substrate, copper layer, and processing conditions were the same as in Example 1. The resulting film only has a passive physical barrier function and no dynamic oxidation enhancement or pore self-repair function.
[0054] The measurement results are shown in Table 1.
[0055] Table 1
[0056] Analysis of experimental conclusions: Examples 1 and 2 employed different types of bifunctional ligands for self-assembly passivation treatment. Both ligands retained a bifunctional synergistic structure of catechol consolidation and aromatic amine oxidation response, stably achieving interface protection and dynamic self-reinforcing effects. Both groups of samples formed a structurally complete passivated nanolayer with oxidation-adaptive properties, exhibiting stable overall protective and conductive performance. Comparative Example 1 served as a blank control without a passivation layer. Experimental results showed that bare copper was highly susceptible to rapid oxidation and corrosion pitting under high temperature, high humidity, ultraviolet, and alkaline environments, ultimately leading to near-complete loss of conductivity. Comparative Example 2 served as a pure solvent blank control, using only pure methanol immersion without adding any functional ligands. The results indicated that simple methanol treatment could not form an effective protective structure on the copper surface; the sample continued to pit and its performance significantly degraded. Comparative Example 3 used a monofunctional ligand lacking key active groups, failing to form an adaptive reconstruction structure and only exhibiting a passive barrier effect. Its protective performance rapidly declined after long-term service, confirming that the bifunctional synergistic structure is the core key to ensuring long-term adaptive protective performance.
[0057] Examples 3 and 4, by adjusting the ligand concentration, both yielded continuous, defect-free passivation films, effectively improving the corrosion resistance of copper current collectors. The appropriate concentration range ensured uniform adsorption and sufficient coordination growth of ligand molecules, preventing incomplete film formation due to excessively low concentrations and structural defects due to excessively high concentrations. Comparative Examples 4 and 5 showed that when the ligand concentration was too low, the ligand loading was insufficient, failing to form a complete film, resulting in numerous exposed sites on the copper layer and a significant decrease in protective capability. When the ligand concentration was too high, the ligands tended to aggregate disorderly, causing uneven film thickness, microscopic defects, and poor interfacial bonding and protective uniformity.
[0058] Examples 6 and 7 verified the suitability of the immersion passivation time. Within this appropriate time, as the immersion time increased, the ligand coordination reaction became more complete, the passivation film structure became denser with fewer pores, and the long-term corrosion protection capability gradually improved. Short-time immersion can prepare an ultra-thin passivation layer, suitable for normal operating conditions with extremely low conductive loss; long-time immersion can obtain an extremely dense film layer, suitable for extreme operating conditions such as high temperature, high humidity, and saline-alkali environments. Comparative Examples 6 and 7 show that when the immersion time is too short, the coordination reaction is incomplete, the film layer is incomplete and discontinuous, and effective protection cannot be formed; when the immersion time is too long, the ligands are excessively accumulated, the film layer becomes redundantly thickened, and the internal stress increases, making it prone to cracking and peeling. This not only fails to improve performance but also reduces product stability and process economy.
[0059] For the compatibility test of the copper layer deposition process, Example 5 adopted a preparation process of thermal evaporation combined with low-temperature annealing. The resulting current collector interface exhibited strong bonding, excellent mechanical stability and corrosion resistance, and a high degree of matching with the electroplating process of Example 1. This demonstrates that the ligand self-assembly passivation technology of the present invention does not rely on a single copper layer preparation process and can be adapted to mainstream composite copper current collector processing systems. This is because annealing treatment can eliminate internal stress in the copper layer, optimize surface smoothness, and facilitate the uniform coordination and bonding of ligand molecules, resulting in strong process compatibility and mass production applicability.
[0060] Comparative Example 8 uses a traditional small molecule static passivation process. The protective film structure prepared is fixed, loose and porous. It can only achieve passive protection by physical barrier and does not have environmental response and self-reinforcing ability. It is prone to premature failure under corrosive, high temperature and ultraviolet conditions. It generally suffers from the problem of difficulty in achieving both protection and conductivity and insufficient durability.
[0061] In summary, this invention employs a ligand oxidation adaptive structure protection method, forming a dual protective effect of initial ultra-thin and dense barrier protection and dynamic autonomous reinforcement under harsh operating conditions. While preserving the excellent electrical and thermal conductivity of pure copper to the greatest extent, it significantly improves the corrosion resistance, high-temperature resistance, UV aging resistance, and bending resistance of the composite copper current collector, effectively overcoming the inherent shortcomings of traditional passivation which relies solely on passive protection. The overall technical advantages are significant. Experimental results show that Example 1 exhibits the best overall performance, combining excellent protective effect, stable conductivity, ample process tolerance, and good mass production adaptability. All examples within reasonable parameter ranges stably achieve the core performance effect of this invention, while comparative examples with parameters exceeding the defined range, lacking the core structure, or using a process system other than that of this invention all show varying degrees of performance failure. This invention relies on the synergistic oxidation adaptive structure of bifunctional ligands and bifunctional groups to overcome the shortcomings of traditional passivation protection methods. It can be adapted to various ligand types and copper layer preparation processes. While ensuring the high conductivity of the composite copper current collector, it achieves long-term adaptive corrosion protection under complex working conditions. It effectively solves the practical problems of easy corrosion, poor stability and short service life of traditional products, and has high engineering application value and mass production and promotion prospects.
[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent substitutions, and improvements made by those skilled in the art to the above embodiments without departing from the scope of the technical solution of the present invention, based on the technical essence of the present invention, shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A composite copper current collector based on an adaptive strategy of ligand oxidation structure, characterized in that, It includes a polymer substrate in the center, copper layers on both sides of the polymer substrate, and ligand passivation nanolayers respectively disposed on the copper layers on both sides. The ligand passivation nanolayer is a structured self-assembled film of bifunctional small molecule ligands, which completely covers and is fixed to the surface of the copper layer. The bifunctional small molecule ligand contains both a catechol active group that can coordinate with copper and an aromatic amine active group that can be oxidized to generate free radical cations, which enables the ligand passivation nanolayer to have an oxidative self-adaptive property that can achieve structural compactness enhancement through group oxidation crosslinking reconstruction under corrosion conditions.
2. The composite copper current collector according to claim 1, characterized in that, The thickness of the polymer substrate is 10–100 μm, the thickness of the copper layer on one side of the polymer substrate is 1–50 μm, and the thickness of the ligand passivation nanolayer is 2–30 nm.
3. The composite copper current collector according to claim 1, characterized in that, The bifunctional small molecule ligand is any one of the following: a three-armed catechol-triphenylamine compound, a naphthol-catechol-amine compound, a triphenylamine-catechol compound, or a triazine-catechol-amine compound.
4. A method for preparing the composite copper current collector based on the ligand oxidation structure adaptive strategy as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1: Cleaning, removing impurities, and drying the polymer substrate for pretreatment; S2: A uniform copper layer is deposited on both sides of the pretreated polymer substrate to obtain a copper composite substrate; S3: The copper composite substrate obtained after depositing the copper layer is placed in a bifunctional ligand solution at room temperature to complete the ligand self-assembly and form the initial ligand passivation nanolayer. S4: After soaking, the composite substrate is cleaned and dried to remove free ligands on the surface, thus obtaining the target composite copper current collector.
5. The method for preparing a composite copper current collector based on an adaptive strategy of ligand oxidation structure according to claim 4, characterized in that, In step S1, the polymer substrate is pretreated by cleaning, removing impurities, and drying as follows: the polymer substrate is ultrasonically cleaned with anhydrous ethanol and deionized water for 10-30 minutes in sequence, and then dried with nitrogen.
6. The method for preparing a composite copper current collector based on an adaptive strategy of ligand oxidation structure according to claim 4, characterized in that, In step S2, the process for depositing a uniform copper layer is any one of magnetron sputtering, electroplating, or thermal evaporation; wherein, after the thermal evaporation deposition process is completed, a low-temperature annealing treatment is performed.
7. The method for preparing a composite copper current collector based on an adaptive strategy of ligand oxidation structure according to claim 4, characterized in that, In step S3, the solvent of the bifunctional ligand solution is methanol, the concentration of the bifunctional ligand solution is 0.01-1 mM, the immersion temperature is 20-25℃, and the immersion time is 10-36 h.
8. The method for preparing a composite copper current collector based on an adaptive strategy of ligand oxidation structure according to claim 4, characterized in that, In step S4, the post-treatment method is as follows: ultrasonic cleaning with anhydrous methanol for 5-10 minutes to remove uncoordinated free ligands, and finally drying with nitrogen at a constant temperature.
9. An electrode sheet, characterized in that: The composite copper current collector includes the ligand oxidation structure adaptive strategy as described in any one of claims 1 to 3.
10. A battery, characterized in that: It includes the electrode sheet as described in claim 9.